Discretionary Authority of the Indonesian National Police in the Implementation of Demonstrations - Asba, Patahillah; Wahyu, Moh. Eka (Amsir Law Journal, 2023)
This study aimed to find out the provisions for the use of the discretionary authority of the police as regulated in laws and regulations and to find out the operational standards for implementing police discretion in securing demonstrations/demonstrations. The type of research used in this research was normative research. The results of this study indicated that the provisions for the use of the discretionary powers of the Police are regulated in Article 5, paragraph 1, letter a number 4 of Law Number 8 of 1981 concerning the Criminal Procedure Code, Article 16, paragraph 1, Article 5 paragraph 1 letter a number 4 of Law Number 8 of 1981 concerning the Criminal Procedure Code and Article 16 paragraph 1 of Law Number 2 of 2002. And operational standards for the implementation of Police discretion in securing mass actions when expressing opinions in public (demonstrations), namely the Dalmas unit is prohibited from carrying sharp weapons or firearms, mobile units by order of the commander and in a unit bond. Dalmas members are prohibited from arguing with the masses (submitted by the negotiating team), using the “T Stick” only to encourage the masses not to beat, using hollow bullets and rubber bullets at the request of the regional head of regional police and carried out by the action unit, and checking individual/unit equipment. ___ References Books with an author: Arifin, Z. (2020). Penggunaan Diskresi Kepolisian Dalam Pengamanan Penyampaian Pendapat Dimuka Umum (Unjuk Rasa) Ditinjau dari Aspek Hak Asasi Manusia. Tegal: Universitas Pancasakti Tegal. Muladi. (2002). Politik dan Sistem Peradilan Pidana. Semarang: Badan Penerbit Universitas Diponegoro. Rahardjo, S. (2010). Penegakan Hukum Progresif. Jakarta: Penerbit Buku Kompas. Rahardjo, S. (2007). Membangun Polisi Sipil: Perspektif Hukum, Sosial, dan Kemasyarakatan. Jakarta: Gramedia Pustaka Utama. Sampara, S., and Husen, L. O. (2016). Metode Penelitian Hukum. Makassar: Kretakupa Print. Wahyu, Moh. Eka. (2022). Tinjauan Hukum Diskresi Kepolisian Dalam Pengamanan Demonstrasi di Polres Sidenreng Rappang. Parepare: Fakultas Hukum Institut Ilmu Sosial dan Bisnis Andi Sapada. Journal articles: Arif, M. (2021). Tugas dan fungsi kepolisian dalam perannya sebagai penegak hukum menurut Undang-Undang Nomor 2 Tahun 2002 tentang kepolisian. Al-Adl: Jurnal Hukum, 13(1), 91-101. Asba, P., Syahril, M. Akbar Fhad., & Makkarawa, I. (2022). The Pollution of The Role of The Polri in The Prevention of Commotion in Demonstration. Traditional Journal of Law and Social Sciences (TJLSS), 1(2), 53–72. Asriyani, A., & Dwiyanti, A. (2022). Efektivitas Kepolisian dalam Melakukan Penyelidikan Tindak Pidana Penipuan Online Melalui Media Elektronik Internet. Jurnal Litigasi Amsir, 10(1), 140-145. Manalu, S. (2020). Analisis Yuridis Tindakan Diskresi Kepolisian pada Tahap Penyidikan. Fiat Iustitia, 1(1), 109-125. Purwanda, S., Bakhtiar, H. S., Miqat, N., Nur, R., & Patila, M. (2022). Formal Procedure Versus Victim's Interest: Antinomy of Handling Sexual Violence Cases In East Luwu. Jurnal Hukum Volkgeist, 6(2), 116-122. Widodo, P., & Baharudin, B. (2022). Implementation of Community Policing Program using Problem-Solving Approach by Bhabinkamtibmas. Amsir Law Journal, 4(1), 32-41.